2017
DOI: 10.3389/fpls.2017.01671
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones Improve Plant Growth, Photosynthesis, and Alleviate Oxidative Stress under Salinity in Rapeseed (Brassica napus L.) by Regulating Gene Expression

Abstract: Rapeseed (Brassica napus L.) is a very important edible oil crop in the world, and the production is inhibited by abiotic stresses, such as salinity. Plant hormones can alleviate the stress by regulating the physiological processes and gene expression. To study the plant responses to salinity in combination with GR24, a synthesized strigolactone, the oilseed rape variety (Zhongshuang 11) replications were grown in the pots in a controlled growth chamber under three levels of salinity (0, 100, and 200 mM NaCl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(91 citation statements)
references
References 59 publications
6
85
0
Order By: Relevance
“…These findings collectively provided important clues regarding the potential of SLs in regulating plant responses and adaptation to environmental stresses. Thus, an increasing number of studies have recently focused on the implications of SLs in the adaptation of plants to environmental constraints and have reported many novel findings (Bu et al, ; Cooper et al, ; C. V. Ha et al, ; Liu et al, ; Lv et al, ; Ma et al, ; Ruiz‐Lozano et al, ; Umehara et al, ; Visentin et al, ; Y. Zhang, Lv, & Wang, ). Moreover, the connection of SLs in AM symbiosis‐mediated improvement of physiological responses has also been reported in plants under abiotic stresses, such as high salinity and drought (Aroca et al, ; Ruiz‐Lozano et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings collectively provided important clues regarding the potential of SLs in regulating plant responses and adaptation to environmental stresses. Thus, an increasing number of studies have recently focused on the implications of SLs in the adaptation of plants to environmental constraints and have reported many novel findings (Bu et al, ; Cooper et al, ; C. V. Ha et al, ; Liu et al, ; Lv et al, ; Ma et al, ; Ruiz‐Lozano et al, ; Umehara et al, ; Visentin et al, ; Y. Zhang, Lv, & Wang, ). Moreover, the connection of SLs in AM symbiosis‐mediated improvement of physiological responses has also been reported in plants under abiotic stresses, such as high salinity and drought (Aroca et al, ; Ruiz‐Lozano et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the ABA-deficient mutants up14 (maize), notabilis and sitiens (tomato), the transcriptional levels of the SL synthesis genes CCD7 and CCD8 are reduced, which leads to decreased content of SLs in root secretion [141]. Further, SL synthesis is regulated by ABA in Arabidopsis [41]. KARs negatively regulate seed germination by inhibiting GA synthesis and promoting ABA synthesis in soybean [100].…”
Section: Sl or Kar Crosstalk With Abscisic Acidmentioning
confidence: 99%
“…In recent years, substantial evidence has demonstrated that SLs and KARs are involved in the regulation of the plant responses to abiotic stress [8,37,38,[41][42][43]46,63,143,190,191] (Table 1). SL levels are finely modulated under various types of abiotic stress.…”
Section: Dynamic Regulation Of Sls Under Abiotic Stressesmentioning
confidence: 99%
See 2 more Smart Citations